A Fast and Accurate Calculation Method of Line Breaking Power Flow Based on Taylor Expansion - Li, Shuaihu; Zhao, Xiang; Liang, Wenju; Hossain, Md Tanjid; Zhang, Zhidan (Frontiers in Energy Research, 2022)
In order to quickly obtain the voltage value of each node after the power system line is disconnected, a fast and accurate calculation method of breaking voltage based on Taylor series expansion is proposed in this paper, which can calculate the value of nodal voltage of the system in a short time. At first, a breaking parameter is introduced into the admittance of the disconnected line, and a nonlinear disconnection function is constructed about the breaking parameter. After the line is disconnected, the voltage of each node and the admittance matrix of each node are functions with respect to the relevant parameters, and then the Taylor series is used to expand. Take the voltage of each node of the system before breaking as the initial value of the Taylor series, and the first, second and third derivative of the node voltage with respect to the parameter as the correction term, calculate the voltage of each node of the system after the line is disconnected. Finally, the simulation results of the IEEE 14-node system are used to verify the correctness of the proposed method.